Nigeria and the African Continental Free Trade Agreement Area (AFCFTA): Issues, Challenges and Prospect. - Mustapha, Ayodele Haruna; Adetoye, D. (Advances in Social Sciences Research Journal, 2020)
In order to improve intra-continental trade in Africa Union (AU) introduced the African Continental Force Trade Agreement Area (AFCTFA) to create single continental market for the free movement of goods and services within the African Continent. AU is progressively eliminating tariffs as well as non-tariff barrier to African trade through the AFCFTA which will make it easier for African businesses to trade within the continent and benefit from growing African market. Nigeria’s position on the AFCFTA remains that African economic and social integration must be rules-based and with built-in safeguard against injurious practices. AFCFTA is an important part of the AU – 2063 Agenda to promote economic and social integration on the continent. Agreement comprises of the framework, the protocols for trade in goods and trade in services and the mechanism for dispute resolution. AFCFTA is to facilitate economic growth and diversification through preferential access to Africa’s market. The paper examines Nigeria’s stands which states that continental aspirations must compliment Nigeria’s national interest which includes not positioning it as a dumping ground for finished goods. The paper makes use of secondary source of data to elicit information while it examines the challenges like how will the agreement be implemented on the ground without the necessary infrastructure being built without the procedural issues that makes corruption very possible at the borders. The paper adopts free trade theory to midwife the study.